Advances and Innovations in Brain Arteriovenous Malformation Surgery. (1st February 2014) - Bendok, Bernard R.; El Tecle, Najib E.; El Ahmadieh, Tarek Y.; Koht, Antoun; Gallagher, Thomas A.; Carroll, Timothy J.; Markl, Michael; Sabbagha, Randa; Sabbagha, Asma; Cella, David; Nowinski, Cindy; Dewald, Julius P.A.; et al.
Abstract: Arteriovenous malformations (AVMs) of the brain are very complex and intriguing pathologies. Since their initial description by Luschka and Virchow in the middle of the 19th century, multiple advances and innovations have revolutionized their management and surgical treatment. Here, we review the historical landmarks in the surgical treatment of AVMs and then illustrate the most recent and futuristic technologies aiming to improve outcomes in AVM surgeries. In particular, we examine potential advances in patient selection, imaging, surgical technique, neuroanesthesia, and postoperative neuro-rehabilitation and quantitative assessments. Finally, we illustrate how concurrent advances in radiosurgery and endovascular techniques might present new opportunities to treat AVMs more safely from a surgical perspective.